Alternative to formaldehyde in artificial diet for sugarcane borer and its effects on the parasitoid - Eduardo, Wellington Ivo; Moraes, Renato Franco Oliveira de; Almeida, Luiz Fernando Veloso; Santos, Josy Aparecida dos; Santos, Rafael Ferreira dos; De Bortoli, Sérgio Antônio (Comunicata Scientiae, 2018)
The formaldehyde used as anti-contaminant agent in artificial diets of insects can cause serious risks to human health. However, there are products with the same purpose, but with less toxicity to humans. In this sense, the aim of this study was to evaluate the biological parameters of Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Crambidae) fed on an artificial diet containing different anti-infective agents to replace the formaldehyde, as well as analyze the effects on its parasitoid Cotesia flavipes (Cameron, 1891) (Hymenoptera: Braconidae). The experiment was conducted under a completely randomized design, studying the anti-contaminant agents: sodium benzoate, potassium sorbate, 2-phenylphenol, and formaldehyde (standard diet), with deionized water as control. The larvae of sugarcane borer were fed on diets with the cited agents, and were daily observed for: larval and pupal periods, larval and pupal viabilities, number of unviable larvae, longevity, pupae weight, sex ratio and the adults fecundity. To analyze the effects of the anti-contaminant agents on the C. flavipes parasitoid, 50 larvae of sugarcane borer were parasitized and daily observed until the parasitoid pupae formation, being evaluated: number of adults emerged per pupal mass, longevity and sex ratio. D. saccharalis larvae are positively influenced by replacing formaldehyde to 2-phenylphenol in their diet, not causing significant deleterious effects to C. flavipes.